DESIGN AND SIMULATION OF THE PROCESS OF MAKING STRAIGHT GEARSUSING THE MASTERCAM X5 TO GENERATE G-CODE - rizki, fahri; Santosa, Aa (Universitas Majalengka, 2023)
ABSTRACTIn its development, every manufacturing industry increasingly makes people think more creatively and are faced with new problems, especially in making new innovations. The purpose of these production issues is to achieve faster and more efficient production targets. The metal machining process is an important factor to support the quality of the final product, but there is one obstacle that must be faced.The process of making gears is currently being done not only using a milling machine, there are many machines that are used to produce gears, to reduce the error rate in the process of making wheels using a CNC machine, a simulation is carried out using the Master Cam program. technology produced using software assistance to speed up work and make products better in terms of accuracy and effectiveness. The use of technology in the manufacture of products in various industrial fields continues to be developed in order to increase efficiency. This is also the case with the ceramics industry, which has been increasingly being used as a ceramicshousehold needs. In the production process, the Machining industrygradually using automated processes to replace processesmanuals. The purpose of this research is to analyze the manufacture of gears using a CNC machine.The results of this study are expected to be a reference in making gearsusing a CNC machine. Analysis of machining processes performed includes machining parameters, time and yield or productThis research is an application of the CAD CAM course, the Mastercam software application is very helpful in mold making innovation.